Estimation of genetic distance of rabbit by morphometric analysis - B Brahmantiyo; H Martojo; S.S Monsjoer; Y.C Raharjo (Indonesian Center for Animal Research and Development (ICARD), 2006)
The observation on morphological body conformation of English Spot (ES), Flemish Giant (FG), New Zealand White (NZWm), and Rex (Rexm) from Magelang, Central Java, and New Zealand White (NZWb), Rex (Rexb), Satin (Satin) and RS (RS) from Balitnak-Ciawi, were carried out to determine estimation of Mahalanobis genetic distance. This research was held in Magelang (Central Java) and Balitnak-Ciawi (West Java), 237 heads of Rabbits were used. Eleven different body parts were measured, those were head (length and width), ear (length and width), chest (girth, depth, and width), humerus length, radius-ulna length, tibia length and body length. General Linear Models were used in this observation (SAS package program). Simple discriminant analyses as further analyses were done for head (length and width), chest (girth, depth, and width), humerus length, radius-ulna length, tibia length and body length. ES, FG and NZWm rabbits had morphological size bigger than others. Mahalanobis genetic distance showed that NZWm and NZWb, Rexm and Rexb were had differences with genetic distances of 5.89139 and 6.75571 respectively. Rabbits from Magelang and from Balitnak were different on morphometric with mahalanobis distance of that region ranges were 4.89426 to 6.96749. Results from canonical analysis showed that the most discriminant variables were obtained by chest girth, chest width and humerus length on first canonical and head length on second cannonical. Key Words: Rabbit, Genetic Distance, Morphometric